The Analysis of Setting In Isaac Asimov’s “I, Robot” and “Foundation” - Xayatovna, Niyazova; Anvarovna, Ashurova (Pubmedia Social Sciences and Humanities, 2025)
This article examines the setting features in two key works by Isaac Asimov “I, Robot” and “Foundation”. It explores how the setting influences character development and the development of central themes in the works, such as moral dilemmas, the ethics of artificial intelligence, problems of civilization survival, and the role of knowledge. In “I, Robot” the focus is on the relationship of humans and robots within an already existing society, while in Foundation the large-scale galactic setting serves as a backdrop for analyzing political and historical processes.